Load Frequency Control of Two Area Interconnected Shipboard Microgrid Power System Using PID and Fuzzy Based Controllers - Mushraf, Dania (Thapar Institute of Engineering and Technology, 2025)
The increasing environmental issues and declining availability of fossil fuels have positioned renewable energy as a highly feasible replacement for traditional energy sources. A power system (PS) that integrates distributed generation units, particularly renewable energy sources and storage devices, is referred to as a microgrid (MG). Within marine power applications, MGs enhance electrical efficiency, improve supply reliability, and ensure better power quality. Incorporating Renewable Energy Sources (RESs) into shipboard power systems not only strengthens system stability and operational efficiency but also reduces generation costs and supports environmental sustainability. RESs, however, have the problem of grid security and maintenance. As RES prominence grows, industrial concerns regarding frequency quality have increased. Because RES are inherently intermittent, they can cause a constant supply-demand mismatch, causing the system frequency to fluctuate about the required nominal value with unacceptable quality of response. This unpredictability of the RESs has an impact on the frequency regulation and system generation demand balance. Only by utilizing energy storage systems (ESSs) like batteries, flywheels, or supercapacitors (SC) can this system instability be avoided. The MPS will become more reliable and power quality will be maintained with the aid of these energy storage devices with RESs. This study integrates Renewable Energy Sources (RES) with the Shipboard Microgrid (SMG) of a two-area power system to address frequency regulation challenges. Proposed model considers an interconnected system that incorporates photovoltaic (PV), wind, and fuel cell (FC) generation, supported by supercapacitors and battery storage. For control, both a PID controller and a Fuzzy Logic Controller are employed to mitigate frequency deviations and regulate tie-line power exchange. Without controllers, the frequency error fails to return to zero; therefore, a PID controller with automatic tuning is applied to reduce the Area Control Error (ACE) and improve system dynamics. Further enhancement is achieved through the application of an FLC, which refines the transient response. The developed MATLAB/Simulink test model successfully demonstrates that frequency deviations remain within acceptable limits, while overshoot is significantly reduced.
Keywords: Load Frequency; Ship board microgrid; PID cotroller; Fuzzy Controller; Power system